Clinical Characteristics of Asymptomatic Patients with SARS-CoV-2 in Zhejiang: An Imperceptible Source of Infection - Wei Dai; Xinmiao Chen; Xiaoting Xu; Zhefeng Leng; Wenwen Yu; Hui Lin; Huiying Li; Jie Lin; Zhangwei Qiu; Yuanrong Dai (Canadian Respiratory Journal)
Objective. Coronavirus disease 2019 (COVID-19), caused by the novel coronavirus SARS-CoV-2, was first identified in December 2019 in Wuhan, China, and has since spread globally, resulting in an ongoing pandemic. However, the study of asymptomatic patients is still rare, and the understanding of its potential transmission risk is still insufficient. In this study, epidemiological investigations were conducted in the Zhejiang province to understand the epidemiology and clinical characteristics of asymptomatic patients with COVID-19. Methods. This retrospective study was carried out on 22 asymptomatic patients and 234 symptomatic patients with COVID-19 who were hospitalized in Zhejiang Duodi Hospital from January 21 to March 16, 2020. The characteristics of epidemiology, demography, clinical manifestations, and laboratory data of mild patients were compared and analyzed. Results. The median age was 28 years in asymptomatic patients and 48 years in symptomatic patients. The proportion who were female was 77.3% in asymptomatic patients and 36.3% in symptomatic patients (p<0.001). The proportion of patients with coexisting diseases was 4.5% in asymptomatic patients and 38.0% in symptomatic patients (p=0.002). The proportion of patients with increased CRP was 13.6% in the asymptomatic group and 61.1% in the symptomatic group (p<0.001). The proportion of patients received antiviral therapy was 45.5% in the asymptomatic group and 97.9% in the symptomatic group (p<0.001). The proportion of patients received oxygen therapy was 22.7% in the asymptomatic group and 99.1% in symptomatic patients (p<0.001). By March 16, 2020, all patients were discharged from the hospital, and no symptoms had appeared in the asymptomatic patients during hospitalization. The median course of infection to discharge was 21.5 days in asymptomatic patients and 22 days in symptomatic patients. Conclusions. Asymptomatic patients are also infectious; relying only on clinical symptoms, blood cell tests, and radiology examination will lead to misdiagnosis of most patients, leading to the spread of the virus. Investigation of medical history is the best strategy for screening asymptomatic patients, especially young people, women, and people without coexisting disease, who are more likely to be asymptomatic when infected. Although the prognosis is good, isolation is critical for asymptomatic patients, and it is important not to end isolation early before a nucleic acid test turns negative.